2018
DOI: 10.1051/epjconf/201816702004
|View full text |Cite
|
Sign up to set email alerts
|

Graphite oxide based targets applied in laser matter interaction

Abstract: Abstract.In the present work, we propose the production of a hybrid graphene based material suitable to be laser irradiated with the aim to produce quasi-monoenergetic proton beams using a femtosecond laser system. The unique lattice structure of the irradiated solid thin target can affect the inside electron propagation, their outgoing from the rear side of a thin foil, and subsequently the plasma ion acceleration. The produced targets, have been characterized in composition, roughness and structure and for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The PDMS thickness and density were 5 μm and 1.011 g/cm 3 , respectively. The thickness of the foils was determined by microbalance weighing using a Mettler Toledo Micro-Balance with 1-μg absolute accuracy 16 A preliminary slit (S0) reduces the heat load of the ion beam on the object collimator (S1) whereas two Faraday cups monitor the beam current before and after S1. The object collimator (S1) regulates the beam spot size, the fast deflector (DF) controls the beam blanking F I G U R E 1 A, The picture and B, the scheme of the ion microbeam line.…”
Section: Experimental Sessionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PDMS thickness and density were 5 μm and 1.011 g/cm 3 , respectively. The thickness of the foils was determined by microbalance weighing using a Mettler Toledo Micro-Balance with 1-μg absolute accuracy 16 A preliminary slit (S0) reduces the heat load of the ion beam on the object collimator (S1) whereas two Faraday cups monitor the beam current before and after S1. The object collimator (S1) regulates the beam spot size, the fast deflector (DF) controls the beam blanking F I G U R E 1 A, The picture and B, the scheme of the ion microbeam line.…”
Section: Experimental Sessionmentioning
confidence: 99%
“…The PDMS thickness and density were 5 μm and 1.011 g/cm 3 , respectively. The thickness of the foils was determined by microbalance weighing using a Mettler Toledo Micro‐Balance with 1‐μg absolute accuracy 16 and the density by pycnometer method .…”
Section: Experimental Sessionmentioning
confidence: 99%
“…The prepared foils were characterized using different analysis techniques, such as X-ray photoelectron spectroscopy (XPS), SEM, Raman spectroscopy, characteristic X-ray fluorescence induced by electron beams (EDX), Rutherford backscattering spectroscopy (RBS) and elastic recoil detection analysis (ERDA) [15][16][17]. The composition of the pristine GO and of the thermal reduced GO and some properties are reported in table 1.…”
Section: Jinst 15 C03056mentioning
confidence: 99%
“…The choice of GO and reduced GO (rGO) as material to be laser irradiated, is based on their characteristics of materials at low density, high mechanical resistance with tailored electrical conductivity. Alongside the graphene-based materials, Torrisi et al, [8] revealed promising prospects of GO in the generation, in vacuum, of hot and dense plasmas from which the emitted ion streams can be accelerated and employed for several applications from fundamental research [9] to hadrontherapy [10]. Unfortunately, the maximum proton energy produced by high energy pulsed laser (ps duration) is less than 100 MeV, which is far from the energy necessary for full hadron-therapy program sustainability.…”
Section: Introductionmentioning
confidence: 99%